2014
DOI: 10.3329/jhpn.v31i4.20050
|View full text |Cite
|
Sign up to set email alerts
|

Access and Barriers to Immunization in West Bengal, India: Quality Matters

Abstract: performance (7). The maintenance of time schedule has been considered crucial proxy indicator of the quality of coverage of immunization (7-9). The other possible ways to look into the quality of immunization is to consider the availability of manpower, equipment, and drugs (10-12). The results of studies in Africa and Asia report that the quality of vaccination services still leaves much to be improved in developing countries (12). They found that the principal problems in maintaining the quality in vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…The population's hesitancy was discovered to be because of a lack of accurate knowledge about the vaccine. This agrees with the findings of Dutta et al, who found that a child with a working mother is almost half as likely to be vaccinated as a child whose mother is unemployed [25] . Our findings contradicted those of Deborah et al, who found that vaccine optimism increased as educational levels increased and safety concerns decreased [26] .…”
Section: Discussionsupporting
confidence: 93%
“…The population's hesitancy was discovered to be because of a lack of accurate knowledge about the vaccine. This agrees with the findings of Dutta et al, who found that a child with a working mother is almost half as likely to be vaccinated as a child whose mother is unemployed [25] . Our findings contradicted those of Deborah et al, who found that vaccine optimism increased as educational levels increased and safety concerns decreased [26] .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, lower SES showed a higher likelihood of vaccine hesitancy in similarity to observations by previous authors. 12,14 Among the characteristics of children, the gender of the child and birth order was found to be significantly associated with vaccine hesitancy in the present study. This is similar to findings from some of earlier studies.…”
Section: Discussionsupporting
confidence: 45%